2021
DOI: 10.1136/bmjopen-2020-045570
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Parent Carers programme: mixed methods process evaluation and refinement of a health promotion intervention

Abstract: ObjectivesParent carers of children with special educational needs or disability are at risk of poorer mental and physical health. In response to these needs, we codeveloped the ‘Healthy Parent Carers’ (HPC) programme. This study examined the views and experiences of participants in the HPC feasibility trial to inform programme refinement.Intervention, setting and participantsHPC is a peer-led group-based intervention (supported by online materials) for primary carers of disabled children, encouraging behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Building on our earlier findings, which established satisfaction with the in‐person programme and programme and workshop participant reports of improved health and wellbeing, the current study demonstrated that it was feasible for trained staff from two different Delivery partner organisations to implement a programme developed by a research team 27,38 . This research suggests that delivering the programme online is a feasible and acceptable mode of delivery and potentially creates more accessibility and reach and may reduce costs.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Building on our earlier findings, which established satisfaction with the in‐person programme and programme and workshop participant reports of improved health and wellbeing, the current study demonstrated that it was feasible for trained staff from two different Delivery partner organisations to implement a programme developed by a research team 27,38 . This research suggests that delivering the programme online is a feasible and acceptable mode of delivery and potentially creates more accessibility and reach and may reduce costs.…”
Section: Discussionsupporting
confidence: 58%
“…Delivery partner organisations to implement a programme developed by a research team. 27,38 This research suggests that delivering the programme online is a feasible and acceptable mode of delivery and potentially creates more accessibility and reach and may reduce costs. This study enabled the creation of a promising Implementation Package and logic model.…”
Section: Authors Contributionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The potential for peer-to-peer parent support was suggested in the review [ 46 , 48 ] and has been shown to be beneficial in other studies of parents/caregivers caring for children with long-term conditions [ 81 ]. Benefit may result from structured group-based intervention to support the health and well-being of parents/caregivers, as already established for parents/caregivers of disabled children [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents in our study expressed a preference for anticipatory information to be provided by a peer they could relate to, who had the time to explain things to them using language they understood, who listened to them, supported them to ask questions, and who boosted their confidence in being able to manage mild-to-moderate bronchiolitis at home. Peer-to-peer support for parents of children with long-term conditions has been shown to provide grounded reassurance and support that parents value as it comes from people who have a lived understanding of their situation [ 44 , 45 , 46 ]; this strongly resonates with the value placed on the Parent Champion appreciating the challenges they faced.…”
Section: Discussionmentioning
confidence: 99%